Psychological empowerment of health professionals - Salles, Bianca Gomes (2020)
Objective: To assess whether there are differences in psychological empowerment betweendifferent health professionals working in a teaching hospital.Method: A comparative, quantitative, and cross-sectional study carried out with165 professionals selected at random and who worked in a teaching hospital in the inland of thestate of São Paulo. The participants were divided into three groups: 1) nurses, 2) physicians,and 3) other professionals (physiotherapists, psychologists, pharmacists, speech therapists,social workers, and nutritionists). For data collection, a form was used to characterize thesample, as well as the Brazilian version of the Psychological Empowerment Instrument. Tocompare the scores between the three groups, the Kruskal-Wallis test was used, followed byDunn' post-test.Results: Nurses, physicians, and other professionals scored 71.4; 69.3, and71.1 points (p=0.5959), respectively, in the total score of the instrumentConclusion: There are no statistically significant differences in the perception of psychologicalempowerment of different health professionals.Conclusion: There are no statistically significant differences in the perception of psychologicalempowerment of different health professionals.Keywords: Power, psychological. Health personnel. Clinical competence. Nursing.